Prevalence and factors associated with body image dissatisfaction among university students: repeated surveys analysis - Thiago Ferreira de Sousa; Sueyla Ferreira da Silva dos Santos; Amanda Silva Rodrigues; Camila Bosquiero Papini; Diego Augusto Santos Silva; Sheilla Tribess (Universidade Federal de Santa Catarina, 2019)
Body image dissatisfaction may favor the onset of disorders such as anorexia and bulimia. The aim of this study was to compare the prevalence of body image dissatisfaction between two surveys and to assess sociodemographic factors and link with university associated with body image dissatisfaction due to overweight and thinness. Two cross-sectional studies were carried out with samples of 1,085 and 1,041 public higher education institution students in years 2012 and 2014, respectively. The body silhouette scales measured body image dissatisfaction due to overweight and thinness. Sociodemographic variables (sex, age and marital status) and link with the university (study shift, university time and study areas) were the independent variables. Comparisons between surveys were performed using the Chi-square test and the association between variables by Odds Ratio (OR). Results: There was an increase in the prevalence of body image dissatisfaction in students of the Engineering area between surveys. In 2012, younger males presented lower chances of dissatisfaction due to overweight and higher chances of dissatisfaction due to thinness (OR: 2.06; 95%CI: 1.50-2.84). In 2014, younger men with no partner (OR: 2.06; 95%CI: 1.50-2.84), enrolled in the 2nd year of university of the Health Sciences area (OR: 0.49; CI95%: 0.25-0.97) presented lowers chances of presenting dissatisfaction due to overweight. Conclusion: The prevalence of body image dissatisfaction due to overweight between surveys is higher in men and was associated with lower chances of dissatisfaction due to overweight in both surveys and in younger students.